Perioperative antithrombotic management in degenerative spine surgery: a multicenter cohort of 767 consecutive patients - Giuseppe Corazzelli; Sergio Corvino; Davide De Los Rios; Diego Gentile; Chiara Di Domenico; Francesco Corazzelli; Gennaro De Rosa; Francesco Fiore; Cristiana Germano; Marco Filippelli; Niccolò Colella; Francesco Ricciardi; et al. (Frontiers in Medicine, 2026)
Background Perioperative management of antithrombotic therapy in degenerative spine surgery remains a challenging clinical issue, particularly in elderly patients with cardiovascular comorbidities requiring chronic anticoagulant or antiplatelet treatment. Although several guidelines address perioperative anticoagulation in high–bleeding-risk procedures, procedure-specific evidence in elective spinal surgery remains limited, and clinical practice is still heterogeneous. Methods A multicenter retrospective cohort study was conducted including 767 consecutive patients aged 60 years or older who underwent elective surgery for degenerative spine disease. Surgical procedures included anterior cervical discectomy and fusion, lumbar microdiscectomy for disc herniation, decompression for lumbar spinal stenosis, and monosegmental posterior lumbar interbody fusion. Patients were stratified according to perioperative antithrombotic management into three groups: no chronic antithrombotic therapy, perioperative low-molecular-weight heparin substitution, and temporary perioperative substitution with low-dose aspirin. Intraoperative hemoglobin loss, operative time, postoperative length of stay, and perioperative complications were compared across groups. Results Perioperative outcomes were similar among the three antithrombotic management groups across all procedures. Intraoperative hemoglobin loss, operative duration, and postoperative hospitalization showed no significant differences between patients undergoing low-molecular-weight heparin substitution or aspirin continuation and those without chronic antithrombotic therapy. No cases of postoperative spinal epidural hematoma requiring evacuation, myocardial infarction, stroke, deep venous thrombosis, or pulmonary embolism were observed. The observed between-group differences in hemoglobin loss, operative time, and postoperative hospitalization remained within the predefined clinically meaningful margins. Conclusion In this multicenter cohort of 767 consecutive patients undergoing common degenerative spine procedures, perioperative antithrombotic management based on low-molecular-weight heparin substitution or low-dose aspirin substitution was not associated with clinically relevant worsening of perioperative outcomes when compared with patients not receiving chronic antithrombotic therapy. These findings suggest that structured perioperative antithrombotic protocols may represent a reasonable strategy in elective degenerative spine surgery.